A companion to the works of Johann Gottfried Herder - Adler, Hans; Köpke, Wulf; Herder, Johann Gottfried von (Studies in German literature, linguistics, and culture, 2009)
Herder's life and works / Steven D. Martinson -- Herder's epistemology / Marion Heinz and Heinrich Clairmont -- Herder and historical metanarrative : what's philosophical about history? / John Zammito -- Herder's concept of humanität / Hans Adler -- Herder and language / Jürgen Trabant -- Herder's aesthetics and poetics / Stefan Greif -- Myth, mythology, new mythology / Ulrich Gaier -- Particular universals : Herder on national literature, popular literature, and world literature / Karl Menges -- Herder's views on the Germans and their future literature / Wulf Koepke -- Herder's Biblical studies / Christoph Bultmann -- Herder's theology / Martin Kessler -- Herder and politics / Arnd Bohm -- Herder's poetic works, his translations, and his views on poetry / Gerhard Sauder -- Herder's style / Hans Adler -- Herder as critical contemporary / Robert E. Norton -- Herder in office : his duties as superintendent of schools / Harro Müller-Michaels -- Herder's reception and influence / Günter Arnold, Kurt Kloocke, and Ernest A. Menze